System to Support Decisions for the Enhancement of Post Graduate Studies: Analytical Skills as a Focus - Mohammed, Anmar A. (2010)
The main aim of this study is to research and improve the unsatisfactory materials that currently available for understanding and making use of student's background as a base to support decision making. This study proposed to develop an interactivity-based Decision Support System (DSS) prototype for post graduate students who are pursuing their study in Information Technology. According to the literature, the programming skill is considered an important skill in the current economy and the future knowledge economy, added that there are many graduates who does not possess skills in programming due to several factors. The prototype will assist decision makers in making decisions in regards to the current intake.